Research of GPS Anti-Jamming Based on Circular Antenna Array - Ruihui Di; Honglei Qin; Xiaobai Li (Data Science Journal, 2007)
In this paper, a new model for suppressing jammers to GPS receivers is proposed. In the model, circular antenna arrays combining minimum norm (min-norm) and linearly constrained minimum variance (LCMV) algorithms have been used for signal anti-jamming. Six GPS signals' and two jammers' original incident direction were assumed respectively. The simulation was performed with a variation of the power of the two jammers and the element number of the circular antenna array. The simulation result indicates that by utilizing this new signal suppression model, nulls depths assigned to the jammer reach -238dBW when the number of element of circular antenna array is assumed to be 30. It also indicates that the stronger power of the jammer, the deeper nulls depths can be assigned with this new signal processing structure.